2007
DOI: 10.1002/pat.1012
|View full text |Cite
|
Sign up to set email alerts
|

Reactive compatibilization of nylon copolymer/EPDM blends: experimental aspects and their comparison with theory

Abstract: In situ reactive compatibilization was first time applied to a low melting nylon (nylon 6 and 66 copolymer) and EPDM blend system. The effects of in situ compatibilization and concentration of compatibilizer on the morphology and mechanical properties of nylon/EPDM blends have been investigated. The influence of EPM-g-MA on the phase morphology was examined by the scanning electron microscopy (SEM) after preferential extraction of the minor phase. The SEM micrographs were quantitatively analyzed for domain siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The leveling off or decrease in mechanical properties above a critical compatibilizer content is common in polymer blends. 13,39,40 It is believed that below the optimum level, the interface is not saturated with compatibilizer. Above the optimum level, the compatibilizer saturates the interface, 16 and some compatibilizer stays outside the interface; this is not its function, and may lead to lower homogeneity of the whole blend.…”
Section: Optimization Of the Compatibilizer Contentmentioning
confidence: 99%
“…The leveling off or decrease in mechanical properties above a critical compatibilizer content is common in polymer blends. 13,39,40 It is believed that below the optimum level, the interface is not saturated with compatibilizer. Above the optimum level, the compatibilizer saturates the interface, 16 and some compatibilizer stays outside the interface; this is not its function, and may lead to lower homogeneity of the whole blend.…”
Section: Optimization Of the Compatibilizer Contentmentioning
confidence: 99%
“…Thermoplastic polyamide (PA)-based TPEs with nonpolar or polar rubbers as the second components, such as ethylene-propylene diene terpolymer, [1][2][3][4][5][6][7][8] ethylene-propylene rubber, 9 natural rubber, 10 butadiene-acrylonitrile copolymer, [11][12][13][14][15][16][17] hydrogenated butadiene-acrylonitrile copolymer, 18-21 acrylate rubber, [22][23][24] and halogenated butyl rubber 17,[25][26][27][28] have been investigated intensively by applying dynamic vulcanization technique, and the resultant PA-based TPEs have found wide applications in sports, transport, and construction areas.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] The compatibilizers may be block, graft or random copolymers whose segments are chemically identical to or having affinity with the polymer components. [15][16][17][18][19][20] There has been much research about some compatibilizers applied in the polar and nonpolar polymer blends. Wootthikanokkhan and Tongrubbai 21 had reported that poly(isoprene-butyl acrylate) block copolymers were used as compatibilizers in natural/acrylic rubber blends.…”
Section: Introductionmentioning
confidence: 99%